2006
DOI: 10.1063/1.2234315
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of phosphorus diffusion by carbon co-implantation

Abstract: The impact of Si interstitial (Sii) flux suppression on the formation of P junctions by rapid thermal annealing (RTA) is demonstrated. Here we investigate the role of amorphization coupled with C co-implantation on P diffusion and its activation. From experiments on C co-implants in a-Si versus c-Si, we conclude that only a small fraction of C interacts with Si interstitials (Sii). We have demonstrated that optimization of implants followed by spike RTA yields extensions suitable for gate lengths of 30nm, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…[122][123][124][125] Interestingly, in Si codoping P and C lead to the suppression of the diffusion of P. 124 Regarding the impact of carbon on the diffusion of donor atoms in Ge, this was clarified by diffusion experiment 36 and DFT studies. 48 In particular, in an experimental diffusion study, Brotzmann et al 36 determined that codoping with carbon leads to a reduction of the diffusivity of the donor atoms (P, As, and Sb) (see Fig.…”
Section: 119120mentioning
confidence: 99%
“…[122][123][124][125] Interestingly, in Si codoping P and C lead to the suppression of the diffusion of P. 124 Regarding the impact of carbon on the diffusion of donor atoms in Ge, this was clarified by diffusion experiment 36 and DFT studies. 48 In particular, in an experimental diffusion study, Brotzmann et al 36 determined that codoping with carbon leads to a reduction of the diffusivity of the donor atoms (P, As, and Sb) (see Fig.…”
Section: 119120mentioning
confidence: 99%
“…For a given implant species, energy and dose, the product Rs · X J tends to be insensitive to variations in the annealing conditions and can thus be used to find X J for the present Rs data by interpolation (±20% estimated uncertainty). Estimates of X J for experiment I, based on prior studies for the annealing of P, 26 As, 27 BF 2 , 28,29 and B 30 implants, are shown in Table V. Junction depth analysis thus affirms that the activated layers are generally shallower than the depth of penetration of the heating radiation.…”
Section: Discussion Of Resultsmentioning
confidence: 83%
“…The depths of the electrically activated layers after rapid thermal annealing were estimated from sheet resistance and dopant concentration profiles that had been determined in previous work by secondary ion mass spectroscopy. [26][27][28][29][30] The depth to which the dopants diffuse after RTA is defined by a junction depth parameter, X J , which is defined as the depth at which the dopant volume concentration falls to 10 18 cm -3 . For a given implant species, energy and dose, the product Rs · X J tends to be insensitive to variations in the annealing conditions and can thus be used to find X J for the present Rs data by interpolation (±20% estimated uncertainty).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Therefore, phosphorus did not exhibit evident diffusion. Such mechanism has been used to form ultrashallow phosphorus junctions with carbon implantation [17][18][19]. This also implies that interstitial generation did not significantly affect phosphorus deactivation, according to the deactivation behavior shown in Fig.…”
Section: Resultsmentioning
confidence: 94%